STUDI PARAMETRIK PERKUATAN GALIAN DALAM PADA TANAH LEMPUNG MENGGUNAKAN DINDING DIAFRAGMA DAN SECANT PILE - Ayu Sinta Aprilia; Rahmat Kurniawan; Syahidus Syuhada; Try Lestari Sihotang; Ahmad Auliadi Yufrizal; Puspa Ningrum (LPPM Universitas Abdurrab, 2026)
The selection of deep excavation retaining systems in Indonesian clay soils is commonly performed based on practical experience without systematic parametric guidance. This study develops selection criteria between diaphragm walls and secant piles through a comprehensive parametric study using the finite element method. A total of 216 numerical models were simulated using Optum G2 software, varying wall type (diaphragm wall and secant pile), excavation depth (4, 8, and 12 m), groundwater table position, building surcharge load (25 kN/m), soil type (soft clay with N-SPT = 4 and stiff clay with N-SPT = 15), and constitutive model (Mohr-Coulomb and Hardening Soil). Results demonstrate that the Hardening Soil model produces 30–39% lower deformations compared to Mohr-Coulomb. Secant piles proved more cost-efficient across all 216 scenarios analyzed, achieving up to 50% cost savings for shallow excavations under low-risk conditions. The most influential parameters on wall performance are, in order: soil type, excavation depth, groundwater table position, constitutive model, surcharge load, and wall type. The resulting design charts and decision matrices serve as preliminary design tools within the SNI 8460-2017 framework.